Corporate income taxation in Ukraine under the conditions of strengthening international exchange of information (Economics and region, 2023)
The article examines the current state of corporate income tax in Ukraine, in particular – categories of tax payers and tax rates applicable to each category, analyses the dynamics of the income tax revenues’ share in GDP and total tax revenues. Current issues of taxation by income tax in the context of strengthening international information exchange and combating tax evasion are considered. In the context of gradual introduction of global practices, tax control over payment of income tax is being strengthened and changes are being implemented into tax legislation. One of the latest changes and risks for taxpayers is the obligation to prepare three-level transfer pricing documentation, which includes local documentation, master file and country-by-country report, enabling tax authorities to obtain information about enterprises that are part of international groups of companies, and their taxable income. The rules for controlled foreign companies in Ukraine provide for a number of new legislative requirements to strengthen control over the payment of corporate income tax. In particular, such rules include the submission of reports, as well as notification to the tax authorities about changes in shares in a controlled foreign company. Council Directive (EU) 2018/822 was developed with the aim of informing tax authorities about cross-border agreements that potentially provide mechanisms for aggressive tax planning and achieving automatic exchange of information between tax authorities of EU member states. Cross-border transactions between several EU countries or between EU countries and non-EU countries (including Ukraine) that meet a number of criteria are subject to mandatory disclosure. The article describes the main content of the concept of business purpose, which is used to prove the reality and economic feasibility of tax payers' reconciliation of transactions with both residents and non-residents. The concept of a business purpose has been actively implemented in transfer pricing. As a result of checking the existence of a business purpose and proving its absence, tax authorities can reduce the costs of the corporate income tax payer and, accordingly, increase the tax base.
Keywords: corporate income tax; exchange of tax information; tax evasion; tax control; business purpose